Dynamics analysis of permanent magnet synchronous motor speed control with enhanced state feedback controller using a linear quadratic regulator - Crescent Onyebuchi Omeje; Ayodeji Olalekan Salau; Candidus Ugwoke Eya (Heliyon, 2024)
This paper presents a robust speed regulation and control of a permanent magnet synchronous motor (PMSM). A linear quadratic regulator (LQR) based state feedback controller was developed to achieve a successful suppression of periodic disturbance of speed and torque. Sliding mode observer in conjunction with the disturbance observer was deployed in the control of motor speed. Simulations were carried out based on two compared controllers such as the state feedback controller and the conventional proportional-integral-derivative (PID) controller to attenuate the noisy effects of the external disturbance. A comparative analysis of results showed that a robust as well as an improved speed and torque dynamic performance was achieved with the state feedback (SFC) controller. A reduced periodic disturbance with percentage steady state error values of 24.17% and 23.51% was obtained with the SFC controller as compared to 38.0% and 38.37% obtained using a PID controller. The Eigen values obtained from the derived state feedback matrix (K) based on Ackerman's rule proved that the entire system operation is controllable and the performance index is marginally stable. All simulations were performed using MATLAB/SIMULINK version 2021.